Exploring the coordination, anti-oxidant, and bacterial behavior of a new azo ligand derived from 4,5-dimethylimidazole with copper and zinc divalent ions - Husham M. Mubark; Israa N. Witwit; Hussein A. Ali Salman; Mohauman M. Al Rufaie (Journal of BioScience and Biotechnology)
New azo ligand synthesized from 4, 5-dimethylimidazole, focusing on its coordination properties with copper and zinc divalent ions. The experimental findings confirmed the formation of octahedral geometrical complexes, where the coordination occurs through one nitrogen atom of azo and an N3 atom of imidazole. Evidence from spectroscopic techniques (13-CNMR, Mass, FT-IR, and UV-Vis), conductivity measurements, and magnetic susceptibility supported the structural integrity of the complexes. Biological evaluation showed that the ligand and its complexes possess notable antibacterial properties, particularly the zinc complex, which exhibited stronger inhibitory effects against both Staphylococcus and E. coli bacteria. Antioxidant tests using the DPPH assay indicated that the ligand effectively scavenges free radicals, achieving 70% inhibition at 25 ppm, making it a promising candidate when compared to ascorbic acid. The results underscore the potential of this ligand and its complexes for applications in medicinal chemistry, especially in the development of antimicrobial and antioxidant agents.